Why is the Roy-Borjas model unable to predict international migrant selection on education? Evidence from urban and rural Mexico - Stefan Leopold; Jens Ruhose; Simon Wiederhold (Halle Institute for Economic Research (IWH), 2023)
The Roy-Borjas model predicts that international migrants are less educated than nonmigrants because the returns to education are generally higher in developing (migrant-sending) than in developed (migrant-receiving) countries. However, empirical evidence often shows the opposite. Using the case of Mexico-U.S. migration, we show that this inconsistency between predictions and empirical evidence can be resolved when the human capital of migrants is assessed using a two-dimensional measure of occupational skills rather than by educational attainment. Thus, focusing on a single skill dimension when investigating migrant selection can lead to misleading conclusions about the underlying economic incentives and behavioral models of migration.
urn:nbn:de:gbv:3:2-981176
Keywords: F22; J24; J61; O15; 330; education; international migration; occupational skills; selection